The Effect of Promotion and Product Quality on Purchasing Decisions Purchasing Anzora Skincare Through E-commerce Shopee in Bandar Lampung - Indriani, Putri; Ali Alam, Iskandar (International Journal of Management Science and Information Technology, 2025)
This study aims to evaluate the effect of promotion and product quality on purchasing decisions purchase of Anzora Skincare through E-commerce Shopee in Bandar Lampung. The number collected in this sample, namely a total of 80 participants through an online questionnaire and data processed through SPSS, is utilized of this study method quantitative approach. Data analysis techniques applied are classical assumption test. The findings of the analysis describe promotion in the context of partial or simultaneous contributions a significant impact on purchasing decisions. significant positive impact on purchasing decisions. And the findings of the analysis explain product quality partially and simultaneously contribute a significant impact on purchasing decisions. This study provides information related to skincare purchasing decisions that emphasize promotion and product quality, so that the benefits of using skincare in facial care.